Cost-effectiveness of utidelone and capecitabine versus monotherapy in anthracycline- and taxane-refractory metastatic breast cancer - Chen, Mulan; Zhang, Heng; He, Xiaoyan; Lin, Yingtao (Frontiers in Pharmacology, 2024)
Background This study aimed to assess the cost-effectiveness of combining utidelone with capecitabine, compared to capecitabine monotherapy, for the treatment of anthracycline- and taxane-refractory metastatic breast cancer within the Chinese healthcare system. Methods A partitioned survival model was formulated based on patient characteristics from the NCT02253459 trial. Efficacy, safety, and health economics data were sourced from the trial and real-world clinical practices. We derived estimates for costs, quality-adjusted life years (QALYs), and the incremental cost-effectiveness ratio (ICER) for the two treatment strategies. Sensitivity and subgroup analyses were conducted to rigorously evaluate uncertainties' impact. Results Over a 5-year span, the combination therapy manifested substantially higher costs than capecitabine monotherapy, with a differential of US$ 26,370.63. This combined approach conferred an additional 0.49 QALYs, resulting in an ICER of US$ 53,874.17/QALY. Utilizing the established willingness-to-pay threshold, the combination might not consistently be deemed cost-effective when juxtaposed against monotherapy. However, at an ICER of US$ 53,874.4/QALY, the probability of the combination being cost-effective increased to 48.97%. Subgroup analysis revealed that the combination was more cost-effective than capecitabine alone in specific patient groups, including those <60 years, patients with more than two chemotherapy rounds, patients lacking certain metastases, patients having limited metastatic sites, patients with an Eastern Cooperative Oncology Group status of 0, and patients with particular hormone receptor profiles. Conclusion Although the combination of utidelone and capecitabine may not be an economically viable universal choice for anthracycline- and taxane-refractory metastatic breast cancer, it could be more cost-effective in specific patient subgroups than capecitabine monotherapy.